Network analysis of socioeconomic disparities and public transport in COVID-19 spread: a case study in northeast Brazil - Cavalcante, Taise F; Barboza, Waneska de S; dos Santos, Cliomar A; Araújo, Adriano Antunes de S; Quintans-Júnior, Lucindo José; Martins-Filho, Paulo Ricardo (The Journal of Infection in Developing Countries, 2024)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted public transportation systems worldwide. In this study, we evaluated the rate of COVID-19 positivity and its associated factors among users of public transportation in socioeconomically disadvantaged regions of Brazil during the pre-vaccination phase of the pandemic. Methodology: This ecological study, conducted in Aracaju city in Northeast Brazil, is a component of the TestAju Program. This initiative was designed to expand COVID-19 testing to asymptomatic individuals in public spaces such as squares and bus terminals. Using logistic regression, we examined the relationship between COVID-19 positivity and factors such as demographics, socioeconomic status, and travel frequency. The Fruchterman-Reingold algorithm was used to explore transmission pathways across neighborhoods with varying living conditions. Results: Of the 1,420 public transport users tested via real time reverse transcriptase polymerase chain reaction (RT-PCR), 249 were positive, indicating a 17.5% positivity rate (95% CI: 15.7–19.6). Our findings revealed a higher positivity rate during periods of increased viral spread (OR = 4.3, 95% CI: 3.1–5.9) and in neighborhoods with poorer conditions (OR = 1.5, 95% CI: 1.1–2.1). Network analysis revealed affluent neighborhoods as significant transmission hubs of the disease. Conclusions: Our study highlights the vital role of urban mobility patterns in the spread of COVID-19. Neighborhoods with better living conditions that serve as hubs of activity and movement, enable gatherings and interactions among people from diverse regions, including those from areas with higher infection rates.